1996
DOI: 10.1111/j.1467-8543.1996.tb00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Relations in Hotels and Catering: Neglect and Paradox?

Abstract: Given that hotels and catering comprise an importantpart of the service sector representing the changing face of the economy, their neglect in industrial relations discourse about the 'new' industrial relations is no longer sustainable. Previously unpublished data from the Workplace Industrial Relations Survey 1990 (WIRS3) have provided the first opportunity for systematic analysis and evaluation of employment relationship issues in the industry and finds them to be different from those observed elsewhere in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 62 publications
(92 citation statements)
references
References 34 publications
5
86
1
Order By: Relevance
“…(The foreign-owned hotels were also large empoyers, ranging in size from 117 to 404 employees, with an average of 265.) Although there was a considerable range, many establishments only reported employing fairly small numbers of part-time staff, contrary to typical profiles of the industrty's workforce (Lucas, 1996). The majority of respondents (87%) indicated that the numbers of full-time staff did not vary significantly throughout the year, suggesting relatively little adjustment to seasonal fluctuations.…”
Section: The Sample Hotelsmentioning
confidence: 89%
See 2 more Smart Citations
“…(The foreign-owned hotels were also large empoyers, ranging in size from 117 to 404 employees, with an average of 265.) Although there was a considerable range, many establishments only reported employing fairly small numbers of part-time staff, contrary to typical profiles of the industrty's workforce (Lucas, 1996). The majority of respondents (87%) indicated that the numbers of full-time staff did not vary significantly throughout the year, suggesting relatively little adjustment to seasonal fluctuations.…”
Section: The Sample Hotelsmentioning
confidence: 89%
“…' (1995, p. 27) Second, ownership of the hotel company also emerges as an important factor, with foreignowned firms apparently taking a more enlightened approach. Lucas andLaycock (1991, 1992) argue that there is evidence of foreignowned firms pursuing a more sophisticated approach. Price (1994, p. 58) also claims that these untis are more sophisticated in their approach to the management of people than their UK counterparts, and goes on to argue that the improvements evident in larger establishments were 'to counter the potential threat posed by foreign-owned international hotel groups which are already increasing their share of the UK market'.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Lucas (1996) has argued that the almost daily demand¯uctuations within the UK sector provide the basis for a workforce substantiated by part-time and casual workers from the secondary labour market. Together with high labour turnover levels such conditions provide probably the key barriers to unionisation within the industry (Byrne, 1986;Gabriel, 1988).…”
Section: The Structure Of the Hotel Industrymentioning
confidence: 99%
“…Furthermore, contrary to popular perception the serious injury rates of hotel workers were found to be four times higher than those recorded amongst construction workers and correlated directly to low levels of unionisation (Cully et al, 1998). It is an industry then that, as Lucas (1996) argues, re¯ects an`extreme example of British industrial relations' (Lucas, 1996, p. 268), which might best be portrayed by Sissons' (1993, p. 207)`bleak house' typology.…”
Section: Introductionmentioning
confidence: 96%